2017
DOI: 10.1186/s40560-016-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-induced coagulopathy and critical bleeding: the role of plasma and platelet transfusion

Abstract: Hemorrhage is responsible for 30 to 40% of all trauma-related mortality. Among adult trauma patients, 94% of hemorrhage-related deaths occur within 24 h and approximately 60% of these deaths within 3 h of hospital admission. Therefore, appropriate initial fluid resuscitation for bleeding is crucial to avoid preventable traumarelated death. In particular, the resuscitation strategy must be designed to complement prompt correction of anemia, coagulopathies, and thrombocytopenia. Conventional damage control resus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…While platelet count predicts outcome, transfusing platelets based on platelet count to “normalize” platelet count does not seem to improve outcomes, and may even harm patients, if the internal environment is hostile [21]. The appropriate transfusion trigger for platelets in injured patients remains to be elucidated but goal-directed platelet transfusions with TEG MA have been associated with a reduction in platelet transfusions and a reduction in mortality in patients undergoing massive transfusion [7,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…While platelet count predicts outcome, transfusing platelets based on platelet count to “normalize” platelet count does not seem to improve outcomes, and may even harm patients, if the internal environment is hostile [21]. The appropriate transfusion trigger for platelets in injured patients remains to be elucidated but goal-directed platelet transfusions with TEG MA have been associated with a reduction in platelet transfusions and a reduction in mortality in patients undergoing massive transfusion [7,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…The new tendencies report Fibrinogen and BE ( 46 , 49 - 50 ) as individual predictors of MT, which stand out because they diminish early, even before the other coagulation factors ( 49 ) . The prothrombin time (PT) and the activated partial thromboplastin time (aPTT) ( 46 , 51 ) , among others, used to determine Acute Traumatic Coagulopathy (ATC) are examined using the PROMMTT sample ( 52 ) and its subsequent investigations ( 34 , 46 , 53 ) , which show their alteration but do not determine a fixed interval with regard their definition.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that the disorder of the body's internal environment and the production and release of platelet antibodies in patients with leukemia would affect the maturation of platelets and cause damage to them, leading to a decrease in the number of platelets in patients (21). Platelet transfusion therapy can enhance the intracellular platelet density of patients through matching of blood after transfusion, to prevent the deterioration of patients' condition caused by hemorrhage (22). In clinical practice, CCI, PPR and patients' hemorrhage status were used as the criteria to assess the efficacy of platelet transfusion (23).…”
Section: Discussionmentioning
confidence: 99%